Lullabying in Javanese Caregiver-Infant Interaction: A Discursive-Integrative Pragmatic Approach - Rahardi, R. Kunjana; Firdaus, Winci (Ranah: Jurnal Kajian Bahasa, 2025)
The objective of this research was to depict pragmatic functions of lullabying within the Javanese cultural context, examining how linguistic practices in early infant caregiving facilitate emotional bonding, cultural transmission, and behavioral socialization. Utilizing a qualitative, discursive-integrative pragmatic framework, the research employs multimodal discourse analysis on verbal lullabies collected from digital social media platforms, notably TikTok. Data were collected using the observation method combined with the note-taking technique. Subsequently, the data were analyzed through the application of a contextual analysis method. The results of the analysis reveal five pragmatic functions of lullabying in Javanese caregiving practices. These five functions are as follows: (1) shooting songs using metaphorical language to convey protection and comfort; (2) onomatopoeic refrains that leverage rhythmic repetition to capture attention and induce calm; (3) ludic and culturally embedded references connecting infants to Javanese heritage; (4) vernacular intimacy that subtly guides behavior through affectionate, colloquial speech; and (5) playful nonsense lullabies infused with domestic referentiality to create soothing yet engaging interactions. These findings reveal lullabying as a complex pragmatic performance deeply rooted in Javanese values such as humility, social harmony, and compassion, serving not only as a means of soothing but also as a culturally specific mechanism for early moral and social education. Abstrak Tujuan penelitian ini adalah menggambarkan fungsi-fungsi pragmatik dari aktivitas meninabobokan dalam konteks budaya Jawa, dengan menelaah bagaimana praktik kebahasaan dalam pengasuhan bayi pada tahap awal berperan dalam membangun ikatan emosional, mentransmisikan nilai budaya, serta melakukan sosialisasi perilaku. Dengan menggunakan kerangka pragmatik kualitatif berorientasi diskursif-integratif, penelitian ini menerapkan analisis wacana multimodal terhadap lagu-lagu nina bobo yang dikumpulkan dari media sosial digital, khususnya TikTok. Data dikumpulkan melalui metode observasi yang dipadukan dengan teknik pencatatan. Selanjutnya, data dianalisis menggunakan metode analisis kontekstual. Hasil analisis mengungkap lima fungsi pragmatik dari aktivitas meninabobokan dalam praktik pengasuhan Jawa. Kelima fungsi tersebut adalah: (1) lagu penenang yang menggunakan bahasa metaforis untuk menyampaikan perlindungan dan kenyamanan; (2) refrein onomatope yang memanfaatkan pengulangan ritmis untuk menarik perhatian dan menimbulkan ketenangan; (3) unsur ludik dan rujukan budaya yang menghubungkan bayi dengan warisan Jawa; (4) keintiman vernakular yang secara halus membimbing perilaku melalui tuturan penuh kasih dan bersifat kolokial; dan (5) lagu nina bobo bernuansa “nonsense” yang dipadukan dengan referensialitas domestik untuk menciptakan interaksi yang menenangkan sekaligus menarik. Temuan ini menunjukkan bahwa aktivitas meninabobokan merupakan sebuah performa pragmatik yang kompleks dan berakar kuat pada nilai-nilai Jawa seperti kerendahan hati, harmoni sosial, dan kasih sayang, yang tidak hanya berfungsi untuk menenangkan, tetapi juga sebagai mekanisme khas budaya dalam pendidikan moral dan sosial pada tahap awal kehidupan.